MILESTONES OF VISIBILITY OF NURSING IN THE CONTEMPORARY ERA: A REFLECTION IN THE LIGHT OF WANDA HORTA - Moura, Jefferson Wildes da Silva (2022)
Objective: to reflect on the milestones of nursing visibility in the contemporary era in the light of Wanda Horta. Method: this is a theoretical-reflexive study, based on the theoretical basis of Wanda Horta's assumptions. Results: two central categories were selected: Nursing in the perception of Wanda Horta and Nursing as art and science. Wanda Horta actively participated in the process of transformation of the nursing profession in Brazil, corroborating for systematized care through the development of the Nursing Process, as well as in the scientific of the profession through the elaboration of its theory focused on basic human needs. In addition, he collaborated in the teaching-learning process and training of new nurses, as well as in the dissemination of Nursing as art and science. Final considerations: Horta contributed to the advancement of Nursing in the practical, scientific and professional dimension, revolutionizing nursing care in Brazil.